Effects of different fatty acid supplementation on body weight and haematobiochemical parameters in rat (International Journal of Natural Sciences, 2012)
The effects of some selected fatty acids supplement on hematobiochemical parameters were studied in rat. A total of twenty rats were randomly assigned into four groups. Group A was considered as control and fed with rat pellet. Group B was treated with 20 mg Soybean oil / kg feed, group C with 20 mg Mustard oil/ kg feed and group D with 20 mg Ghee /kg feed. The mean body weight of group B, C and D of 2nd and 3rd observation (30 and 60 days, respectively) was significantly (P> 0.01) higher compared to group A (Control). The highest body weight was observed in 3rd observation and it was 185.00 ± 2.76 g in group D and the lowest was in control group. TLC value of group D increased significantly (P